2020
DOI: 10.1038/s41388-020-1256-x
|View full text |Cite
|
Sign up to set email alerts
|

NCOA5 deficiency promotes a unique liver protumorigenic microenvironment through p21WAF1/CIP1 overexpression, which is reversed by metformin

Abstract: Prevention and treatment options for hepatocellular carcinoma (HCC) are presently limited, underscoring the necessity for further elucidating molecular mechanisms underlying HCC development and identifying new prevention and therapeutic targets. Here, we demonstrate a unique protumorigenic niche in the livers of Ncoa5 +/− mouse model of HCC, which is characterized by altered expression of a subset of genes including p21 WAF1/CIP1 and proinflammatory cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 53 publications
0
38
0
Order By: Relevance
“…Metformin was shown to reduce the HCC incidence in this mouse model while reducing p21 expression in hepatocytes and decreasing the HPC number. Deletion of the p21 gene phenocopied metformin treatment in Ncoa5 deficient mice with regard to the reduced HPC number [ 129 ]. Thus, metformin may reduce HCC risk in the NASH condition partially by inhibiting HPC activation by reducing p21 expression in hepatocytes.…”
Section: Direct Effects and Underlying Mechanisms Of Metformin On Hepatocytes Or Malignant Cells That May Inhibit Nash-related Hccmentioning
confidence: 99%
See 3 more Smart Citations
“…Metformin was shown to reduce the HCC incidence in this mouse model while reducing p21 expression in hepatocytes and decreasing the HPC number. Deletion of the p21 gene phenocopied metformin treatment in Ncoa5 deficient mice with regard to the reduced HPC number [ 129 ]. Thus, metformin may reduce HCC risk in the NASH condition partially by inhibiting HPC activation by reducing p21 expression in hepatocytes.…”
Section: Direct Effects and Underlying Mechanisms Of Metformin On Hepatocytes Or Malignant Cells That May Inhibit Nash-related Hccmentioning
confidence: 99%
“…Long-term metformin treatment decreased the total intrahepatic myeloid cell number and the M2 macrophage incidence in Ncoa5 +/− mice. Metformin seems to regulate both the M1 and M2 population in the NASH condition here, and the mechanism was elusive but was implied to metformin’s repression of p21 expression in the hepatocyte [ 129 ]. In a transgenic zebrafish model of HCC driven by the expression of activated β-catenin, a high-fat diet was found to promote HCC progression.…”
Section: Metformin On the Immune Population That May Indirectly Inhibit Nash-related Hcc Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The kinase inhibitor p21 promotes cell cycle arrest and has anti-proliferative functions. In this special situation, T RM cells were expanded in mice with HCC and decreased in line with HCC reduction [ 102 ]. Another study showed that T RM cells in HCC have an exhausted phenotype, e.g., shown by the expression of PD-1, LAG-3 and TIM3, especially in comparison to T RM cells, which are not in the tumor microenvironment.…”
Section: Liver T Rm Cells—in Health Disease Anmentioning
confidence: 99%